The Importance of TPR (Total Physical Response) Method in Teaching English for beginners - Khandamova Feruza Bakhodirovna (Genius Journals, 2022)
This article’s purposes are to describe the implementation of TPR method in teaching English, to know parts of activities in the implementing of TPR method that make students become more interest and active to the English subject, and to know the students’ response after learning English. This method is qualitative descriptive. The data sources are from teacher and students. The students’ role was as imitators because when the teacher acted out the imperative sentence to the students, they imitated the teacher’s actions physically. They became more active and interest to learn English because the teacher taught them by using imperative drilling and modelling concept that became the basic concept of TPR method.
Keywords: Implementation; TPR Method; verbal communication